Инновациялық технологияларды білім беруде(педагогикада) қолдану - Суюбаева, Ж.Т. (My University, 2016)
In the article the types of innovative technologies are considered and recommendation suggestions over are brought on their use.
Keywords: technology; innovation; multimedia internet; electronic textbook